ANALYSIS OF ENGLISH TEACHER TEACHING READINESS TOWARDS THE IMPLEMENTATION OF MERDEKA CURRICULUM AT SD INPRES SAMBUNG JAWA 3 MAKASSAR - Balawara, Andi Wulan; Muhayyang, Maemuna; Tahir, Muh. (JTechLP: Journal of Technology in Language Pedagogy, 2025)
The aim of this research is to examine how prepared English teacher is for implementing the Merdeka Curriculum at SD Inpres Sambung Jawa 3 Makassar, focusing on the aspects of lesson plan, execution of lessons, and assessment of learning English. By using qualitative research with a case study design, the researcher conducted interview and non-˗participatory observation with one English teacher at SD Inpres Sambung Jawa 3 Makassar. The results of analysis show that (a) the English teacher in implementing the Merdeka Curriculum has fulfilled availability of learning planning aspect which includes understanding of the Merdeka Curriculum, preparation of lesson plans/teaching modules, and student-centered learning plans, (b) the teacher has fulfilled the readiness and availability in aspects of learning implementation including use of active teaching methods, flexibility in learning and use of media and learning resources, and (c) the teacher has fulfilled availability of learning assessment which includes initial assessment, formative assessment, and summative assessment. From this research, it can be concluded in some points: readiness in preparing lesson plans: the results of the interviews indicate that teacher have demonstrated good readiness in preparing lesson plans. They understand the importance of learning outcomes and can prepare appropriate materials, the readiness in the implementation of learning plan: the use of self-designed teaching modules and the integration of games into the teaching and learning process serve as evidence that teachers are able to create a creative learning environment that aligns with students’ interests, and the last is the readiness in assessment: the teacher readiness to assess their students is also evident. They understand and apply assessments to final exams. The result of this research shows that the English teacher at SD Inpres Sambung Jawa 3 Makassar, have a well-prepared readiness in all aspect of the Merdeka Curriculum in the learning planning aspect, aspect of learning implementation, & learning assessment.